Urinary Cortisol Increases During a Respiratory Outbreak in Wild Chimpanzees - Behringer, Verena; Preis, Anna; Wu, Doris F.; Crockford, Catherine; Leendertz, Fabian H.; Wittig, Roman M.; Deschner, Tobias (Frontiers in Veterinary Science, 2020)
In mammals, the excretion of cortisol can provide energy towards restoring homeostasis and is a major component of the stress response. However, chronically elevated cortisol levels also have suppressive effects on immune function. As mounting an immune response is energetically costly, sick individuals may conserve energy by exhibiting certain sickness behaviors, such as declining activity levels. Due to the complex interplay between immune function and sickness behaviors, endocrinological correlates have received growing attention in the medical community; but so far this subject was investigated rarely. Furthermore, given the complexities of studying illnesses and immunity in natural settings, correlates of sickness behaviors have yet to be studied in non-human primates in the wild. Methods: We measured urinary cortisol levels using liquid chromatography-mass spectrometry in a group of wild habituated chimpanzees in Taï National Park, Côte d’Ivoire, before, during, and after a respiratory disease outbreak (main causative pathogen: human respiratory syncytial virus A, with co-infections of Streptococcus pneumoniae). Changes in cortisol levels were then related to urinary neopterin levels, a biomarker of immune system activation. Results: Urinary cortisol levels were found to be more than 10-fold higher during the outbreak in comparison to levels before and after the outbreak period. Increasing cortisol levels were also associated with increasing neopterin levels. Interestingly, rather atypical patterns in diurnal decline of cortisol levels were found during infection periods, such that levels remained raised throughout the day. Conclusion: In conclusion, cortisol increase was related to cellular immune response. Our results suggest that cortisol is a mediator of infectious disease pathogenicity through its impact on the immune system, and that wild chimpanzees may be facing energetic stress when sick. By monitoring immune challenges in wild living animals, our study demonstrates that immune defenses have costs and that these costs are context-specific.